Company Performance Predictions By Agency Cost, Earning Management Using the Z-Score (Case Study in Indonesia) - Irawati, N; Sadalia, I; Marlina, L (KnE Social Sciences, 2018)
Investors play an important role by spending their money in the capital market. Without investors, the stock market do trade securities trading. In choosing a company, investors will evaluate the best condition of the company. So the aim of this research is to investigate whether the agency cost and earning management will give an impact to financial distress. The research object is the company listed in Indonesian Capital Market from 2012 to 2016. The regression analysis used to test the hypothesis was applied only to the final sample of 22 firms at the end of the sample period from 2012 to 2016. This study used the Modified Jones Model to measure discretionary accruals as earning management. And the dependent variables Z-score served as substitutes for financial distress. The hypothesis was tested using a regression model. The first independent variable operating expense ratio as substitutes the agency cost has a negative significant on financial distress. The smaller amount of agency cost will impact the Z-score to increase. This showed that if the Z-score is higher, it will mean that the company is in the area of no financial distress. Then, the second variable earning management has negative relationship but insignificant on financial distress. Keywords: agency cost, earning management, financial distress